Joyful Listening: Integrating 'Nusa dan Rara' Animation and KAHOOT! for Maharah Istima’/Al-Istima` bi al-Farhi: Damju al-Rusum al-Mutaharrikah 'Nusa dan Rara' wa Kahut li Maharah al-Istima’ - Maulana, Muhammad Rifqi; Darmawaty, Ridha; Nurullah Thorieq Faiz Anaam (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to develop learning media for Maharah Istima' skills based on the KAHOOT! application which is equipped with animated videos. This research is motivated by the difficulties faced by students in listening to Arabic, both through audio which is often less clear and fast or because of the difference in sound systems that make it difficult for them to understand. In addition, the lack of vocabulary and attention when listening also become factors that hinder students' understanding. The method used in this research is the ADDIE model, which is applied in the development of learning media based on KAHOOT! with the animated video “Nusa and Rara” at Al-Mumtaza Banjarmasin Islamic Junior High School. This learning media has been validated by media, language, and material experts, with the validation results showing a very good category, namely 92% from media experts, 86% from material experts, and 98% from language experts. Teachers gave a positive response with a validation score of 95%. User trials of students showed satisfactory results, with small group trials reaching 94%. Based on the results of validation and user trials, it can be concluded that the learning media for Maharah Istima' skills based on KAHOOT! which is equipped with an animated video “Nusa and Rara” is very feasible to use for students of Al-Mumtaza Banjarmasin Islamic Junior High School.